Local Content Curriculum Development Policy for Primary Education by the Education and Culture Office in West Sumbawa District - Khusnarti, Khusnarti; Yamin, ,Ahmad; Suparman, Suparman (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research discusses a thesis study on the Local Curriculum Development Policy for Elementary Education by the Department of Education and Culture in West Sumbawa. The objectives of this research are as follows:1. To explain the form of the local curriculum development policy for elementary education in West Sumbawa Regency, and 2. To design the substance of the Local Curriculum for elementary education in West Sumbawa Regency. The research method employed in this study is a qualitative approach. The qualitative research is research that uses a scientific background with the aim of interpreting occurring phenomena and is conducted by involving various existing methods. The study involved 7 experts in oral tradition, arts, and culture in West Sumbawa as informants. Data collection procedures utilized interviews and documentation. Data analysis employed qualitative descriptive analysis. The results of the analysis of the implementation of the local curriculum policy by the Department of Culture and Education in West Sumbawa Regency. The implementation of the policy was developed based on the Republic of Indonesia Law Number 23 of 2014, the Minister of Education and Culture Regulation of the Republic of Indonesia Number 79 of 2014 concerning Local Content in the 2013 Curriculum, the Minister of Education, Culture, Research, and Technology Regulation of the Republic of Indonesia Number 56/M/2022 concerning Guidelines for the Implementation of the Curriculum for the Purpose of Learning Recovery, and the West Sumbawa Regency Regulation Number 85 of 2017 concerning Local Content Curriculum for Elementary Education in West Sumbawa Regency. In addition, this research also discusses the substance used in the development of the local curriculum at the elementary school level in West Sumbawa Regency, including lawas, malangko,ngumang, and bakelong.In conclusion, it can be inferred that the development and implementation of the local curriculum policy have legal support in the process of teaching local content in West Sumbawa Regency, particularly related to the oral traditions of the West Sumbawa community. This research also recommends that the implementation of the local curriculum should not only be limited to elementary school but also needs to be implemented at the junior high school and senior high school levels